The Genus Enterococcus: Between Probiotic Potential and Safety Concerns—An Update - Hanchi, Hasna; Mottawea, Walid; Sebei, Khaled; Hammami, Riadh (Frontiers in Microbiology, 2018)
A considerable number of strains belonging to different species of Enterococcus are highly competitive due to their resistance to wide range of pH and temperature. Their competitiveness is also owed to their ability to produce bacteriocins recognized for their wide-range effectiveness on pathogenic and spoilage bacteria. Enterococcal bacteriocins have attracted great research interest as natural antimicrobial agents in the food industry, and as a potential drug candidate for replacing antibiotics in order to treat multiple drugs resistance pathogens. However, the prevalence of virulence factors and antibiotic-resistance genes and the ability to cause disease could compromise their application in food, human and animal health. From the current regulatory point of view, the genus Enterococcus is neither recommended for the QPS list nor have GRAS status. Although recent advances in molecular biology and the recommended methods for the safety evaluation of Enterococcus strains allowed the distinction between commensal and clinical clades, development of highly adapted methods and legislations are still required. In the present review, we evaluate some aspects of Enterococcus spp. related to their probiotic properties and safety concerns as well as the current and potential application in food systems and treatment of infections. The regulatory status of commensal Enterococcus candidates for food, feed, probiotic use, and recommended methods to assess and ensure their safety are also discussed.